Statute and Implementation: How Phantom Policies Affect Tenure Value and Support. Issue 2 (March 2020) - DeFeo, Dayna Jean; Berman, Matthew; Hirshberg, Diane
Using survey responses from public school teachers and principals in Alaska, this article describes their understanding of tenure statute, and how that understanding affected support, perceived effectiveness, and valuation of tenure. Teachers and principals who inflated tenure protections were more likely to support it; the more teachers inflated tenure protections, the higher dollar value they placed on it. The article discusses the fiscal and policy implications of tenure inflation, noting that this garners the most criticism from education reformers, but concomitantly constitutes cost savings for taxpayers.